Predictive factors for recording the death of women of childbearing age in the Hospital Information System (SIH/SUS), Brazil, 2012–2020 - Juliana Alves Marques; Rosa Maria Soares Madeira Domingues; Marcos Augusto Bastos Dias; Claudia Medina Coeli; Rejane Sobrinho Pinheiro; Valeria Saraceni (Revista Brasileira de Epidemiologia)
ABSTRACT Objective: To estimate the death registration coverage of women of childbearing age (WCA) in the Hospital Information System (SIH), according to the hospital of occurrence and to verify the predictors associated with coverage. Methods: Descriptive ecological study with public data from SIH, Mortality Information System (SIM) and National Registry of Health Establishments (CNES), 2012–2020. Deaths in WCA hospitalizations in SIH were compared to those in SIM. Coverage was calculated by the proportion of deaths in SIH in relation to SIM. Supervised classification models — decision tree and random forest — were used to identify hospital characteristics related to coverage. Results: WCA death registration coverage was estimated at 78.0 and 71.8% after excluding hospitals with >100% coverage. Lower coverage was observed in the North region (67.7%) and higher in the South (76.9%). There was an increase in coverage from 69.0% to 74.4% in the period examined. The main factors predicting coverage were urgency/emergency facility, administrative management level, hospital complexity, proportion of adult beds covered by SUS and teaching activity, with lower coverage in those with an urgency/emergency facility and greater coverage in those of higher complexity, in federal hospitals, those with teaching activity and higher proportion of adult beds covered by SUS. Flaws in the CNES registration were identified in SIM. Conclusion: The coverage of WCA death registration in SIH in the country is high and growing. Regional differences reinforce the need for strategies to improve the quality of information systems.